Anti-Atherosclerosis Effect of Angong Niuhuang Pill via Regulating Th17/Treg Immune Balance and Inhibiting Chronic Inflammatory on ApoE-/- Mice Model of Early and Mid-Term Atherosclerosis - Fan, Qinghong; Liu, Yujuan; Rao, Jiaoyu; Zhang, Zhe; Xiao, Wei; Zhu, Tao; Chai, Xiaomeng; Ye, Kaihe; Ning, Na; Yin, Zhen; Chai, Yushuang; Xu, Yimin; et al. (Frontiers in Pharmacology, 2020)
Angong Niuhuang Pill (ANP) is a well-known patented Chinese medicine which is used for hundreds of years for treating the central nervous system diseases. Atherosclerosis is a poly-aetiological chronic inflammatory vascular disease. Preventing inflammation is fundamental for treating atherosclerosis in early stages. In this study, we investigated the protective effects and possible mechanisms of ANP action on a high-fat diet induced early and mid-term atherosclerosis ApoE-/- mice. The effects of ANP were compared with accepted drug simvastatin. Twelve male C57BL/6J mice were used as the control group, and 60 male ApoE-/- mice were randomly divided into five groups: Model group, Simvastatin group, Low-, Medium-, and High-dose ANP group these groups received, respectively, saline, simvastatin (3.0mg/kg), low-dose ANP (0.25 g/kg), medium-dose ANP (0.50 g/kg), and high-dose ANP (1.0 g/kg), once every other day for 10 weeks. After administration, serum biochemical indices were detected by the automatic biochemical analyzer, the concentrations of IL-6 and IL-10 in the serum were assayed by ELISA, expression levels of IL-1β, TNF-α, MMP-2, MMP-9, CCL2, and its receptor CCR2 in the full-length aorta, and expression levels of transcription factors Foxp3, RORγt in the spleen were assayed via western blotting and RT-qPCR. Flow cytometry was used to analyze Th17 cells and Treg cells. Pathological and histological analysis was completed on aortic root. ANP decreased LDL/HDL ratio, concentrations of IL-6 while increased IL-10 in serum. Moreover, ANP down-regulated the expression levels of IL-1β, TNF-α, MMP-2, MMP-9, CCL2, and CCR2 receptor in the full-length aorta. In addition, ANP decreased Th17 cells and expression levels of transcription factor RORγt, increased Treg cells and expression levels of transcription factor Foxp3. ANP decreased content of collagen fibers and infiltration of inflammatory cells in the aortic root. In conclusion, we demonstrated that ANP has anti-atherosclerosis effects on a high-fat diet induced ApoE-/- mice early and mid-term AS model via regulating Th17/Treg balance, inhibiting chronic inflammation, reducing plaque collagen fibers, and reducing inflammatory cells infiltration, to exert its multi-channel multi-target anti-early and mid-term AS effects.